The neck of flying archosaurs (Amniota, Reptilia) : description, reconstruction and biomechanics - Oliveira, Richard Santos Buchmann de (2022)
Pterosaurs and birds are winged archosaurs that originated in the Mesozoic. Flight allowed representatives of both clades to explore previously vacant niches, and the differentiation of forelimbs into wings made the neck of these animals an active, functional limb used during foraging. Presently, birds have diversified and have necks of varying lengths, which are adapted to different life habits. However, the lack of extant descendants of pterosaurs creates gaps in the knowledge regarding the biology of this group, including its cervical anatomy and biomechanics. Here, we identify and describe the vertebral arrangement and influence of cervical soft tissues on the neck position at rest of extant birds. We then apply this data to establish and infer the neck position at rest and associated cervical soft tissues, and quantify the likely movements performed by the neck musculature of pterosaurs. For that end, we dissected the necks of specimens representing sixteen species of extant birds and used computed tomography scans of the cervical series of the pterosaurs Anhanguera piscator, Azhdarcho lancicollis and Rhamphorhynchus muensteri with three-dimensional preservation of the largest number of vertebral elements. We inferred the cervical muscles forces for pterosaurs by multiplying the thickness of the widest point of the muscle and its stress value. We found that the thickness of the intervertebral cartilage of extant birds varies along the neck and that excluding it can distort reconstructions of the neck of extinct animals. We also recognized sixteen muscles associated with the neck of extant birds. The vertebrae of extant archosaurs and pterosaurs showed evolutionary convergences that allowed us to reconstruct synovial cartilages in joints and ligaments in the latter. According to the angulation of the cervical vertebrae, the pterosaur neck probably had a slightly sinuous shape when in a rest position. Furthermore, we inferred thirteen cervical muscles in pterosaurs. We conclude that in pterosaurs the musculature responsible for the dorsoventral movements of the skull and neck was probably more robust and stronger, as in extant birds, and that less robust muscles were associated with stabilizing the neck or performing additional force for cervical movements